Analysis of the correlation between spatial cognitive abilities and wayfinding decisions in 3D digital environments. Issue 8 (11th June 2021) - Ying, Shen; Zhuang, Yuan; Huang, Lina; Wang, Hong; Yin, Zhangcai
ABSTRACT: Although the effects of spatial abilities on behaviour have recently been a hot topic, wayfinding has received little attentions. Here, the reasons for route selection differences during wayfinding were studied from the perspective of individual competence. The mental rotation (A-MR), abstract reasoning (A-AR), visual short-term memory (A-VSTM), spatial perception (A-SP) and spatial orientation (A-SO) abilities of 52 college students were assessed, and their route selection behaviours were tested in homogeneous and heterogeneous three-dimensional virtual scenes. Finally, the relationships between five abilities and the lengths (R-L) and angles (R-A) of the selected routes were analysed and the R meants route here. The path complexity (weighted combination of R-L and R-A) was also fitted using a partial least-squares model with the five abilities. The A-MR and A-AR had obvious relationships with R-L and R-A, whereas A-SP showed little correlation. Moreover, the A-VSTM and A-SO had a significantly higher impact on route selection in the homogeneous spatial environment than in the heterogeneous one. Although the models passed the significance test, the fitting effect was not satisfactory. The routes were affected by many factors, and these five abilities could not fully explain the route selection behaviour of the individuals.